Neoliberal Co-option of English: A Study of Urduized Terms in Pakistani Magazine Articles through Corpus Approaches - Zahra, Fatima Tuz; Zahra, Tehseen; Abbas, Akhtar (Rivista Italiana di Filosofia del Linguaggio, 2023)
Discursive constructions of social values, culture, and ideology have been emerged as indigenized English in the countries remained British colonies in the past. Linguistic representation of these constructions illustrates individual experiences filtered through cultural preferences. Discourse of the post-1947 context represented Urdu as a solid Muslim identity in both parts of British India (Rehman, 1990). This study aims to investigate English language as practiced in the news discourse. This study traced the emergence of local Urduized words in news reports published in local magazines of Pakistan. This investigation has moved away from traditional standard language concepts towards a closer alliance with the values and priorities of local news establishments in the wake of neoliberalism. Taking a corpus-based linguistic approach, this study examines the semantic macrostructures using van Dijk’s social cognitive model (1985) in the news discourse published in Pakistani newspapers. Blommaert’s sociolinguistics theory (2010) was also used as an additional theory to realize the status of non-native varieties of English in global contexts. LancsBox tools (2021) were used to extract word lists and generate collocation networks of selected words. The study excluded the Urduized English words denoting names of persons, places, or things. The findings indicate that Magazine News Reports (MNR) corpora carried rich local Urduized vocabulary in almost all sections of MNR corpora. These words were Urduized in terms of local socio-cultural entities. In addition, the analysis reveals MNR Corpus’ tendency to emphasize the power of the local journalistic stories, depicting them as the true representative of local social identities and foregrounding the discourse of globalization. The findings show that comparing and exploiting such naturalistic texts can help realize the potential of legitimizing local varieties of English (non-native) used in various parts of the world.